Pertimbangan Hakim terhadap Penolakan Gugatan Pembatalan Perkawinan Karena Adanya Ancaman pada Putusan Pengadilan Agama Tanjung Karang Nomor: 1109/Pdt.G/2023/PA.Tnk - Bunga Rahma; Nunung Rodliyah; Elly Nurlaili; Kasmawati Kasmawati; Sayyidah Sekar Dewi Kulsum (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study discusses the judge’s considerations in rejecting a marriage annulment lawsuit due to coercion, as stated in the Religious Court Decision of Tanjung Karang Number: 1109/Pdt.G/2023/PA.Tnk. The lawsuit was filed by a wife who claimed she was forced into marriage due to threats from her parents, thus requesting an annulment based on Article 27 paragraph (1) of Law Number 1 of 1974 on Marriage. However, the panel of judges rejected the claim. This research aims to examine the legal reasoning behind the judge’s rejection of the annulment and the legal consequences resulting from the decision. The study employs a normative and empirical legal approach with a descriptive qualitative method, using primary legal materials such as legislation and court rulings, as well as secondary data from legal literature and interviews. The results show that the judges rejected the claim because the alleged coercion was not proven to constitute an unlawful threat as defined by law, and the marriage was conducted validly according to legal and religious provisions. The legal implication of this rejection is that the marriage remains valid and binding, and all legal rights and obligations between husband and wife continue to apply.